Synthesis and Decomposition of Parabanic Acid Derivatives - Choi, S.K.; Lee, S.G.; Jung, D.I.; Hahn, J.T. (Asian Journal of Chemistry, 2012)
As a part of a research program related to the synthesis of pharmacologically and agrochemically interesting parabanic acid derivatives, we synthesized imidazolidine-2,4,5-trionylimidazolidine (6), 2-thioxoimidazolidine-1-ylimidazolidine (7), benzo[d]-isothiazol-2-yl imidazolidine-2,4,5-thriones (8a-c), 2-thioxobenzo[d]-isothiazol-2-yl imidazolidine-4,5-dione (9a-c) and 1-benzoimidazole-3-imidazolidine-2,4,5-triones (10a-c), 1-phenylurea (11), 1-ethyl-3-[(3-ethylthioureido)methyl]urea (12) and 1-ethyl-3-[(3-methyl-thioureido)methyl]urea (13) were obtained in basic solution through ultrasound.